2003
DOI: 10.1002/eji.200324228
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PD‐1, PD‐L1, and PD‐L2 expression during normal and autoimmune responses

Abstract: Newer members of the B7‐CD28 superfamily include the receptor PD‐1 and its two ligands, PD‐L1 and PD‐L2. Here, we characterize the expression of PD‐1, PD‐L1, and PD‐L2 in tissues of naive miceand in target organs from two models of autoimmunity, the pancreas from non‐obese diabetic (NOD) mice and brain from mice with experimental autoimmune encephalomyelitis (EAE). In naive mice, proteiexpression of PD‐1, PD‐L1, and PD‐L2 was detected in the thymus, while PD‐1 and PD‐L1 were detected in the spleen. PD‐L1, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
446
2
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 567 publications
(475 citation statements)
references
References 46 publications
21
446
2
6
Order By: Relevance
“…Antibodies specific for IRF-1 and IRF-2 were purchased from Cell Signaling Technology (Beverly, MA). [c-32 P]-ATP and poly(dIdC) 2 were obtained from Amersham Biosciences (Piscataway, NJ). PE-conjugated streptavidin was obtained from Jackson ImmunoResearch (West Grove, PA).…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…Antibodies specific for IRF-1 and IRF-2 were purchased from Cell Signaling Technology (Beverly, MA). [c-32 P]-ATP and poly(dIdC) 2 were obtained from Amersham Biosciences (Piscataway, NJ). PE-conjugated streptavidin was obtained from Jackson ImmunoResearch (West Grove, PA).…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…Costimulatory molecules are important regulators of T cell activation, with B7-1 and B7-2 on APCs interacting with the T cell ligands CD28, to provide positive signals [34], or CTLA-4, to provide negative signals [35]. Two other B7 family members are programmed death ligand 1 (PD-L1) and programmed death ligand 2 (PD-L2), both of which bind PD-1 [36]. Recent studies suggest that these cell surface molecules may be important in macrophagemediated T cell suppression.…”
Section: Control Of Inflammationmentioning
confidence: 99%
“…Recent study by Valentina Dal Secco et al demonstrated that mouse testis sertoli cells express elevated level of PD-1 ligand in vitro, by IFN γ treatment [25] To our knowledge, our study is the first investigation of the contribution of PD-1 in male ASA-related infertility in human subjects. This study raises more interest for further investigation to the mechanism of PD-1/PD-1 ligand interaction in the development of ASA-related infertility.…”
Section: Discussionmentioning
confidence: 57%
“…PD-1 also implicates in negative selection [22], and is crucial for regulation of self-reactive T cells that escape negative selection in the periphery [22]. Studies in mouse models of autoimmune disease have revealed that PD-1: PD-1 ligand interaction not only is important in the inhibition of the primary phase of T cell activation and expansion, but also modulates T cell effector functions upon antigen reencounter [25]. Together, these are indicating the key role of PD-1/PD1ligand ligand interaction in the maintenance of central and peripheral tolerance.…”
Section: Discussionmentioning
confidence: 99%